Implementation of the guided inquiry learning model to train critical thinking skills in senior high school - Muti'atus Sholehatu Nurdiyah; Bertha Yonata (Jurnal Pijar Mipa, 2022)
This research aimed to determine students' critical thinking skills by applying the guided inquiry learning model to the reaction rate material. This type of research is a pre-experimental design, with a One-Group Pretest-Posttest Design. This research was conducted on 36 students in class XI MIPA 6 SMA Negeri 1 Menganti Gresik who had not received material about reaction rates. The outcome of this study indicate that: (1) The application of the guided inquiry learning model at the first meeting got a percentage of 95%, at the second meeting 96% with a very good category; (2) Percentage of relevant activities is higher than irrelevant activities; (3) Students' critical thinking skills were successfully trained with an increase in the test as seen through the average N-gain value on the interpretation indicator of 0.86 (high), the inference indicator of 0.83 (high), the analysis indicator of 0.77 (high), and an explanation indicator of 0.80 (high); (4) Cognitive learning outcomes obtained by students showed an increase between pretest and posttest, with an average n-gain value of 0.84 in the high category and from the results of the paired sample t-test, Sig. (2-tailed) 0.000 < 0.005, so there is a significant difference; (5) Student responses to the applied learning model, namely guided inquiry, were very good with a percentage of 95%. This result indicates that the guided inquiry learning model can train the critical thinking skills of class XI students on the reaction rate material.